2021
DOI: 10.5644/ama2006-124.328
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant Chemotherapy for Breast Cancer: Moving Beyond Pathological Complete Response in the Molecular Age

Abstract: <p>This review focuses on neoadjuvant chemotherapy for breast cancer which introduces practical issues for pathologists, including predicting response, optimising specimen handling, size measurement and assessment of residual disease, and recent advances in management of the axilla. The role of neoadjuvant chemotherapy in breast cancer is increasing, and it has become standard of care for high risk Human Epidermal Growth Factor Receptor 2 positive and triple negative breast cancers. The benefits of the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 115 publications
0
14
0
1
Order By: Relevance
“…Accurate diagnosis of pCR, and determination of the presence and quantification of residual disease, is of prognostic importance and is used to make decisions regarding the need for further local and systemic adjuvant therapy. 45 Chemotherapy also induces changes in the surrounding benign breast tissue. 15,33,46 The background breast often shows pronounced lobular atrophy with associated hyalinisation and sclerosis of remaining acinar units (Figure 4).…”
Section: Changes Following Neoadjuvant Chemotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…Accurate diagnosis of pCR, and determination of the presence and quantification of residual disease, is of prognostic importance and is used to make decisions regarding the need for further local and systemic adjuvant therapy. 45 Chemotherapy also induces changes in the surrounding benign breast tissue. 15,33,46 The background breast often shows pronounced lobular atrophy with associated hyalinisation and sclerosis of remaining acinar units (Figure 4).…”
Section: Changes Following Neoadjuvant Chemotherapymentioning
confidence: 99%
“…If there is any doubt that the correct area has been sampled, or if inadequate clinical information has been provided to accurately locate and sample the previous tumour site, then this should be stated in the report. Accurate diagnosis of pCR, and determination of the presence and quantification of residual disease, is of prognostic importance and is used to make decisions regarding the need for further local and systemic adjuvant therapy 45 …”
Section: Changes Following Neoadjuvant Chemotherapymentioning
confidence: 99%
“…With the advent of novel tracers and pathologic and histologic techniques, the most important nodes, namely, the SLNs, now undergo a more thorough and standardized histopathologic examination, which has improved the rate of detection of isolated tumor cells and micrometastases in these nodes [10][11][12][13]. More recent research has reported their prognostic and survival impact, and adjuvant systemic treatment is recommended [14][15][16]. Magnetic resonance imaging (MRI) is a noninvasive technique that can offer valuable information regarding tissues and organs.…”
Section: Introductionmentioning
confidence: 99%
“… 4 , 5 , 6 Patients with breast cancer often need multiple chemotherapy treatments. 7 , 8 The physical health of patients with breast cancer is severely affected by the somatic side effects of chemotherapy. 9 However, a cognitive decline caused by chemotherapy also affects these patients' quality of life (QOL).…”
Section: Introductionmentioning
confidence: 99%
“…In China, the incidence of breast cancer is 7.33%, which ranks first among malignant tumours in females, with a death rate of approximately 6.9% 4–6 . Patients with breast cancer often need multiple chemotherapy treatments 7,8 . The physical health of patients with breast cancer is severely affected by the somatic side effects of chemotherapy 9 .…”
Section: Introductionmentioning
confidence: 99%